Molecular characterization and pathogenicity of Mycoplasma capricolum subsp. capricpolum from goats in Morocco - Noha Semmate; Zaid Zouagui; Zouhair Elkarhat; Zahra Bamouh; Siham Fellahi; Noursaid Tligui; Zineb Boumart; Ouafaa Fassi Fihri; Mehdi El Harrak (BMC, 2022)
Abstract Mycoplasma capricolum subsp. capricolum (Mcc) is an important etiological agent of contagious agalactia (CA). CA affects small ruminants and is characterized by inducing mastitis, arthritis, kerato-conjunctivitis and respiratory symptoms. The aim of this study was to isolate and characterize Mcc from Moroccan goats with contagious agalactia. A total of 300 Alpine goats were monitored. Serology analysis, molecular identification, and isolation of Mcc were realized from suspected goats. An experimental study was conducted for isolated Mcc to determine their pathogenicity. Thus, clinical observation showed that respiratory symptoms were predominant in young animals, and other symptoms, such as mastitis, keratoconjunctivitis and lameness, were more frequently detected in adult goats. Of the 80 tested blood samples, 28 sera were seropositive for Mcc antibodies. Mcc was identified by polymerase chain reaction (PCR) in milk, lung tissue and synovial liquid samples. The isolation of Mcc was successful through bacterial culture from lung tissue. LppA gene sequence of this strain revealed 98.1% similarity with the reference strain (ATCC 27343), with 11 missense variants. Experimental infection resulted in severe and generalized CA disease in sheep and goats, confirming the high pathogenicity of the Moroccan Mcc isolate.